PRODUKSI TANAMAN TOMAT (Solanum lycopersicum L.) DENGAN PEMBERIAN SP-36 DAN DOLOMIT DI TANAH GAMBUT - Mardaus. Intan Sari. Elfi Yenny Yusuf (Fakultas Pertanian, Program Studi Agroteknologi, 2019)
Reseach the ifluece ofthe produktion of a crop tomatos. By the SP-36 and dolomite in peat soil hasee implementd in the garden experiment the fakulty of agrikulture UNISI Riau provice.During 4month from may to the augustus. reseach purpose the provision of avariety ofdoses to SP-36 and dolomite crop of tomato plants in the lads of peat. Medium used to a SP-36 and dolomite, 200kg SP-36/Ha+2Ton, 200kg SP-36/Ha+3Ton, 200kg SP-36/Ha+4Ton, 250kg SP-36/Ha+2Ton, 250kg SP-36/Ha+3Ton, 250kg SP-36/Ha+4Ton. The experimetwork on this useful the parameter observation the ground, pH tall pland, the age of flower theage ofthe frist fruit, heavy brangkas dry. Data analyzedy by obervation ingerprint variety of(ANOVA) and continiued by test further HSD 5% perpecent during the preparattory pheseof turkey the of various doses of combinasi already afford uprade production crop tomato whit the highest on the in creased production of treatment 250kg SP-36/Ha +4 Tons dolomite/Ha, against the age of flowering recorder on treatment 200kg SP-36/ha+4 Tons dolomite/Ha, the frist crop to the age of the fas test intreatmet 250kg SP-36/Ha+4 Tons dolomite/Ha, talll plant to exist at the level of treatmet 250kg SP-36/Ha+4 Tons dolomite/Ha, on the increase intreatment exsist at the level of pH 4 Ton dolomite/Ha againt brangkasan dry planet on the highest treatment 250kg SP-36/Ha+4 Ton dolomite/Ha.